2013
DOI: 10.1158/0008-5472.can-12-3904
|View full text |Cite
|
Sign up to set email alerts
|

Threshold Levels of ABL Tyrosine Kinase Inhibitors Retained in Chronic Myeloid Leukemia Cells Determine Their Commitment to Apoptosis

Abstract: The imatinib paradigm in chronic myeloid leukemia (CML) established continuous BCR-ABL inhibition as a design principle for ABL tyrosine kinase inhibitors (TKIs). However, clinical responses seen in patients treated with the ABL TKI dasatinib despite its much shorter plasma half-life and the apparent rapid restoration of BCR-ABL signaling activity following once-daily dosing suggested acute, potent inhibition of kinase activity may be sufficient to irrevocably commit CML cells to apoptosis. To determine the sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 45 publications
3
30
0
Order By: Relevance
“…This has subsequently been confirmed by other groups postulating that reduction of pSTAT5 is a sensitive marker for the presence of residual/low concentrations of TKI, rather than reduced CrkL phosphorylation. 26,27 In this study, we have used the optimal washout (OPT wash) method as a model of the effect of TKI availability on Bcr-Abl activation and evaluated the critical factors involved in commitment to TKI-induced cell death. Accordingly, the duration of potent TKI exposure required to commit BCR-ABL1 þ cells to death was investigated in the setting of transient Bcr-Abl kinase inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…This has subsequently been confirmed by other groups postulating that reduction of pSTAT5 is a sensitive marker for the presence of residual/low concentrations of TKI, rather than reduced CrkL phosphorylation. 26,27 In this study, we have used the optimal washout (OPT wash) method as a model of the effect of TKI availability on Bcr-Abl activation and evaluated the critical factors involved in commitment to TKI-induced cell death. Accordingly, the duration of potent TKI exposure required to commit BCR-ABL1 þ cells to death was investigated in the setting of transient Bcr-Abl kinase inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several groups have demonstrated that BCR–ABL transformed cells can undergo apoptosis through prolonged intracellular drug accumulation and retention upon high-dose TKI pulse exposure. 1 , 2 , 3 , 4 , 5 This suggests that a given TKI might still be present at active concentrations in the target cells, although the drug has already been cleared from the patient's plasma. Our group has pioneered the measurement of intracellular TKI accumulation using both direct drug detection and functional read outs.…”
mentioning
confidence: 99%
“…Surprisingly, shKIT significantly enhanced the effects of PPY-A on CML CD34 + colony formation in the absence of SCF (Fig 3B, upper panel). This could reflect persistence of a low level of BCR-ABL1 kinase activity not detected by pCRKL immunoblots (29) or constitutive KIT activation that is independent of BCR-ABL1 kinase activity. Additionally, the band corresponding to pKIT Y721 was not completely abolished by BAW667 or imatinib (Fig.…”
Section: Discussionmentioning
confidence: 99%